2020
DOI: 10.3928/01484834-20200617-07
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationships Among Moral Distress, Moral Courage, and Moral Resilience in Undergraduate Nursing Students

Abstract: Background: Nurses and students face a demanding and fluid health care system that can present overwhelming challenges. Moral distress is a challenge encountered by students who experience complex situations. Certain virtues such as moral courage and moral resilience are necessary to navigate around this phenomenon. Method: Using a descriptive correlational study design, a convenience sample of nursing students distributed among three sites were surveye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
1
36
0
8
Order By: Relevance
“… 38 Authors analyzed the data from 529 nurses to demonstrate the convergent validity and concurrent validity of MDT, and then indicated that MDT has great potential as a screening tool for use in research, evaluating the effectiveness of interventions designed to decrease a nurse’s level of MD. To date, some empirical studies have employed this instrument to examine the level of MD in school nurses 62 , 63 and intensive care unit nurses. 64 , 65 However, the application in other clinical nurses or cultural settings has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“… 38 Authors analyzed the data from 529 nurses to demonstrate the convergent validity and concurrent validity of MDT, and then indicated that MDT has great potential as a screening tool for use in research, evaluating the effectiveness of interventions designed to decrease a nurse’s level of MD. To date, some empirical studies have employed this instrument to examine the level of MD in school nurses 62 , 63 and intensive care unit nurses. 64 , 65 However, the application in other clinical nurses or cultural settings has not yet been reported.…”
Section: Resultsmentioning
confidence: 99%
“…They also found a significant correlation between the nurses’ moral courage and resilience, which is consistent with the present study's findings. On a similar note, Gibson et al (2020) found a direct correlation between nursing students’ resilience and moral courage [ 35 ]. Cerit et al (2021) reported a significant negative correlation between nurses’ death anxiety and ethical sensitivity: elevated ethical sensitivity correlated with reduced death anxiety in the nurses [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Good interpersonal relationships, high academic grades, having a role model, and student satisfaction with their major are characteristics of students with high academic resilience levels (Hwang & Shin, 2018). Emerging studies on moral resilience in nursing students demonstrated significant associations with moral courage, age, and previous degrees (Gibson et al., 2020).…”
Section: Review Of Literaturementioning
confidence: 99%